التراث الإثنو-الأنثروبولوجي في الجزائر من خلال مجلة ليبيكا - بوزيد سبابو, مريم (Changement Social; No 4 (2018): revue change social, 2018)
سنحاول، من خلال تفريغ أعداد مجلة ليبيكا(1953) التي أسسها ليونيل بالو (Lionel Balout) من الجزء الأول الصادر 1953 إلى آخر عدد صدر في عام 1998، رصد الانتاج المعرفي الأنثروبولوجي وموقعه في مجلّة اعتبرت بالأساس مجلة لعلمي الآثار وللكتابات القديمة، إضافة إلى علم ماقبل التاريخ والأنثروبولوجيا الفيزيائيّة. كما نحاول من خلال هذا التدخل معرفة كيفية تشكل أنثروبولوجيا المجتمعات المحلية، أي كيفية فهم ومساءلة مواضيع متعلقة بجوانب الثقافة في عمومها. وهل عكست المجلة المحطات الاجتماعية والثقافية وواكبت تطوراتها، ومامدى مواكبة هذا المنتوج الأنثروبولوجي  "المحلي" للسياق العام للأنثروبولوجيا؟ وفي أي ظروف تم إدراج الدراسات الاثنوغرافية بالمجلة، علما أن الأعداد الأولى (من الجزء الأول، سنة 1953 إلى غاية الجزء الثامن، سنة 1960) لم تكن بها أي دراسة متعلقة باي مجال من مجالات علم الانسان، أي الأنثروبولوجيا. كلمات مفتاحيّة: ليبيكا، أنثروبولوجيا اجتماعية ثقافية، اثنوغرافيا، تراث، ثقافة مادية Through the analysis of  Libyca issues (1953) founded by Lionel Balout, startingwith the first issue in 1953 to the last one in 1998, wewillattempt to detect the anthropological and cognitive product as well as its position in a journal thatis, initially, deemed to be a journal for archeology and ancientwritings in addition to prehistoricstudies and physicalanthropology. Wewilltryalso by this intervention to uncover how the local societies' anthropologyisformed, thatis to say how to understand and question subjects in relation withgeneral culture aspects, did the Journal reflected and followed the development of the social and cultural phases and how far this "local" anthropologicalproductiskeeping up with the generalcontext of Anthropology. Moreover, wewillundertake the circumstancesthatcharacterized the integration of anthropologicalstudieswithin the Journal, giventhat all the first issues (from the first one in 1953 to the eight issue in 1960) weredeprived of anyhuman-relatedstudies, thatis to say " Anthropology''. Keywords: Libyca, social and cultural anthropology, ethnography,heritage, material culture